2002
DOI: 10.4049/jimmunol.169.6.3076
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of “Abbreviated” Complementarity-Determining Regions Containing Specificity-Determining Residues Essential for Ligand Contact to Engineer a Less Immunogenic Humanized Monoclonal Antibody

Abstract: Murine mAb COL-1 reacts with carcinoembryonic Ag (CEA), expressed on a wide range of human carcinomas. In preclinical studies in animals and clinical trials in patients, murine COL-1 showed excellent tumor localization. To circumvent the problem of immunogenicity of the murine Ab in patients, a humanized COL-1 (HuCOL-1) was generated by grafting the complementarity-determining regions (CDRs) of COL-1 onto the frameworks of the variable light and variable heavy regions of human mAbs. To minimize anti-V region r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…In the case of 10E8-0fH/4fL, post-hoc analysis of the 10E8-MPER peptide structure indicated that additional reversions of mutations that do not directly interact with the antigen or CDR regions may be possible (e.g., S2Y, Figure 5). Further, the reversion analysis here was focused solely on framework residues; however, it should also be possible to selectively revert CDR mutations as not all mutations within the CDR regions will be important for antigen recognition or overall antibody structure (33, 34). This process could allow for the generation of partially reverted antibody variants with even lower degrees of mutation and with similar, if not better, neutralization activity as their mature bNAb counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of 10E8-0fH/4fL, post-hoc analysis of the 10E8-MPER peptide structure indicated that additional reversions of mutations that do not directly interact with the antigen or CDR regions may be possible (e.g., S2Y, Figure 5). Further, the reversion analysis here was focused solely on framework residues; however, it should also be possible to selectively revert CDR mutations as not all mutations within the CDR regions will be important for antigen recognition or overall antibody structure (33, 34). This process could allow for the generation of partially reverted antibody variants with even lower degrees of mutation and with similar, if not better, neutralization activity as their mature bNAb counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…[280,281] (Inherent immunogenicity also previously posed a challenge to therapeutic development, however, recent advances-including the development of fully humanized antibodies-have rendered this less of a problem nowadays. [282][283][284] ) Single-domain antibodies times lighter in molecular weight compared to regular IgG antibodies (150-160 kDa). [285] Despite their smaller makeup, sdAbs have proven capable of having similar specificity as normal antibodies, and in some cases have demonstrated greater robustness.…”
Section: Functionalization With Receptor-targeting Ligands For Rmtmentioning
confidence: 99%
“…The murine anti-CEA MAb COL-1 was humanized through 'abbreviated' CDR grafting, referred to as HuCOL-1 ABR . Compared to the CDR-grafted humanized COL-1 (Hu-COL-1), HuCOL-1 ABR shows only a minimal decrease in its antigen-binding affi nity while showing a signifi cant decrease in its reactivity to the sera of patients previously administered murine COL-1 in clinical trials [12] .…”
Section: Humanization By Grafting 'Abbreviated' Cdrsmentioning
confidence: 99%
“…In L-CDR1, the COL-1 sequence differed from the human template X93639 at positions 27, 27d, 28, 29, 30, 33 and 34, of which 27 and 33 are designated as non-SDR positions ( table 2 ). HuCOL-1 ABR , previously developed by grafting 'abbreviated' CDRs, contains a human substitution at position 27 (K27Q), validating this residue as a non-SDR [12] . A variant containing a human substitution at position 33 (M33L) in addition to the one at 27 was generated.…”
Section: Antibody Humanization By Sdr Graftingmentioning
confidence: 99%
See 1 more Smart Citation